2019
DOI: 10.3233/ch-180446
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acute reduction of blood viscosity on endothelial function

Abstract: BACKGROUND:The relationship between blood viscosity (BV) and endothelial function is rather complex. An increase in BV causes an increase in blood flow resistance, with negative hemodynamic effects; on the other hand, a moderate increase in BV causes an increase in wall stress shear (WSS), and consequent beneficial effects. As a matter of fact, the effect of changes in BV on endothelial function is not yet clear. OBJECTIVES: Aim of the present study was to evaluate in-vivo the effects of the acute reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Furthermore, it was recently demonstrated that a ∼2% reduction in Hct had no effect on FMD in middle‐aged, overweight individuals without any additional co‐morbidities (Gnasso et al . 2019). Overall, the relatively small changes in Hct/[Hb] and/or presence of co‐morbidities in these latter studies makes reconciliation of these conflicting data problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was recently demonstrated that a ∼2% reduction in Hct had no effect on FMD in middle‐aged, overweight individuals without any additional co‐morbidities (Gnasso et al . 2019). Overall, the relatively small changes in Hct/[Hb] and/or presence of co‐morbidities in these latter studies makes reconciliation of these conflicting data problematic.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence from animal models demonstrating that the magnitude of conduit artery dilatation is attenuated in response to a haemodilution‐mediated reduction in blood viscosity via an endothelium shear stress mechanism, independent of alterations of blood flow (Melkumyants & Balashov, ; Melkumyants et al., ). However, it is unclear whether a similar physiological response is evident in humans (Giannattasio, Piperno, Failla, Vergani, & Mancia, ; Gnasso et al., ; Nagy, Toth, Roth, & Tarjan, ; Tremblay et al., ). For instance, using the conventional forearm reactive hyperaemic test, Gnasso et al.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, using the conventional forearm reactive hyperaemic test, Gnasso et al. () demonstrated that brachial artery dilatation was preserved after a modest decrease in blood viscosity (∼7.7%), via standard blood donation, in middle‐aged healthy men. This result might be explained by the higher shear rate stimulus observed during forearm reactive hyperaemia, thereby counteracting the reduction in blood viscosity (Gnasso et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations